Profil Kemampuan Berpikir Kritis Peserta Didik pada Materi Pecahan Kelas IV Sekolah Dasar Islam Al Azhar 21 Pontianak - Nurhasanah, Amelia; Bistari, Bistari; Halidjah, Siti (ISLAMIKA, 2024)
This research aims to analyze students' critical thinking skills in class IV Khuldi fraction material at Al Azhar 21 Pontianak Islamic Elementary School. The research method used is a mixed method with a descriptive quantitative research form. The research subjects were 22 class IV Khuldi students and 1 class IV Khuldi teacher. The data collection techniques used are observation, interviews and documentation techniques. Data collection tools used observation sheets and interview guidelines and checked the validity of the data using triangulation techniques. Based on the research results, students' critical thinking skills in the indicators provide a simple explanation in the very good category. It was proven that out of 22 students, there were 17 people in the very good category, 3 people in the fair category, and 2 people in the poor category. In the second indicator, namely providing further explanation, students' critical thinking abilities are in the very good category. It was proven that of the 22 students, there were 18 people in the very good category, 1 person in the good category, and 3 people in the poor category. In the third indicator, namely determining strategy and tactics, students' critical thinking abilities are in the quite good category. It was proven that of the 22 students, there were 8 people in the very good category, 6 people in the good category, 6 people in the fair category, and 2 people in the poor category. In the fourth indicator, namely concluding, students' critical thinking abilities are in the good category. It was proven that out of 22 students, there were 11 people in the very good category, 6 people in the good category, and 5 people in the poor category. Thus, it can be concluded that students' critical thinking skills in class IV Khuldi Islamic Elementary School 21 Pontianak fraction material can be said to be good.